High school sports during the CoVID-19 pandemic: The impact of sport participation on the health of adolescents - McGuine, T. A.; Biese, K.; Hetzel, S. J.; Schwarz, A.; Kliethermes, S.; Reardon, C. L.; Bell, D. R.; Brooks, A.; Watson, A. M. (2022)
Context: During the fall of 2020, some high schools across the US allowed their students to participate in interscholastic sports while others cancelled or postponed their sport programs due to concerns regarding COVID-19 transmission. It is unknown what effect this has had on the physical and mental health of adolescents.